The movida tropical: an overview from within and from musical analysis. (Revista Argentina de Musicología, 2018)
The present article summarizes an update of our research on the movida tropical. This first stage is based on musical analysis, and interviews carried out during our shared daily contact with the actors. We will concentrate our analysis on the hits and how they condition the musical production of the moment, and the songs that define the sound and identity of groups. Besides, we explain the present situation of the movida tropical and ponder its contextual situation, musical production and other aspects that shape this musical movement.